2001
DOI: 10.1289/ehp.01109597
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exposure to disinfection by-products in women of reproductive age living in Corpus Christi, Texas, and Cobb county, Georgia: descriptive results and methods.

Abstract: We conducted a field study in Corpus Christi, Texas, and Cobb County, Georgia, to evaluate exposure measures for disinfection by-products, with special emphasis on trihalomethanes (THMs). Participants were mothers living in either geographic area who had given birth to healthy infants from June 1998 through May 1999. We assessed exposure by sampling blood and water and obtaining information about water use habits and tap water characteristics. Two 10-mL whole blood samples were collected from each participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…At the U.S. Centers for Disease Control and Prevention (CDC) (11,12), NCI, EPA, Health Canada (10), the University of Alberta (Canada) (13), Rutgers University (14,15), and elsewhere, scientists are conducting studies on DBP exposure and uptake in the human body. These investigations will provide more accurate information about individual exposures than the traditionally used water consumption questionnaires and quarterly water treatment plant data.…”
Section: Controlling Dbp Exposurementioning
confidence: 99%
“…At the U.S. Centers for Disease Control and Prevention (CDC) (11,12), NCI, EPA, Health Canada (10), the University of Alberta (Canada) (13), Rutgers University (14,15), and elsewhere, scientists are conducting studies on DBP exposure and uptake in the human body. These investigations will provide more accurate information about individual exposures than the traditionally used water consumption questionnaires and quarterly water treatment plant data.…”
Section: Controlling Dbp Exposurementioning
confidence: 99%
“…Chloroform is formed in treated water by the reaction of chlorine with humic acids and other organic material. Concentrations vary by region, day, and time with reported levels ranging from below detection to maximum values of 100-200 mg/l Backer et al, 2000;Kerger et al, 2000;Lynberg et al, 2001;Gordon et al, 2006). Bench-scale experiments have shown that heating tap water gradually (as in a hot water heater) or boiling can affect point of use levels.…”
Section: Introductionmentioning
confidence: 99%
“…Using a mass balance approach, water use data, and exposure factor assumptions including 1 mg/l tap water chloroform, McKone (1987) estimated that showering contributes up to 50% of lifetime chloroform inhalation exposures for the average US adult versus spending time in the bathroom or remainder of the house. Additionally, recent biomarker studies of US adults show that showering/bathing is significantly associated with increases in breath and/or blood chloroform, while other household water use activities such as washing dishes or clothes are not (Weisel et al, 1999;Backer et al, 2000;Lynberg et al, 2001;Nuckols et al, 2005;Xu and Weisel, 2005). Swimming in chlorinated pools is also associated with elevated biomarker concentrations though most studies have been conducted outside the United States (Lindstrom et al, 1997;Le´vesque et al, 2000;Erdinger et al, 2004;Caro and Gallego, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Meaningful exposure occurs through water ingestion, inhalation, and dermal absorption (Weisel and Jo, 1996;Backer et al, 2000;Lynberg et al, 2001). Although several studies have conducted maternal interviews to obtain information on water consumption and detailed residence information (Shaw et al, 1991;Savitz et al, 1995;Waller et al, 1998;Klotz and Pyrch, 1999), most have based exposure assessment solely on the maternal residence at delivery (Kramer et al, 1992;Aschengrau et al, 1993;Bove et al, 1995;Kanitz et al, 1996;Gallagher et al, 1998;Dodds et al, 1999;Kallen and Robert, 2000;Yang et al, 2000;Jaakkola et al, 2001).…”
Section: Introductionmentioning
confidence: 99%